Environmental and economic evaluation of algal-based biofuels through geographically resolved process and sustainability modeling - Quiroz, David, author; Quinn, Jason C., advisor; Windom, Bret, committee member; Willson, Bryan, committee member; Reardon, Kenneth, committee member (Colorado State University. Libraries, 2023)
Advanced algal renewable fuels have been the subject of extensive research during the last decades. Their advantages over conventional biofuel feedstocks position algal biomass as a promising feedstock for the development of a sustainable and circular bioeconomy. Despite recent technological improvements, techno-economic analyses (TEAs) show that algae-derived fuels fail to be cost-competitive with petroleum fuels. Moreover, results from life-cycle assessments (LCAs) indicate declining greenhouse gas emissions when compared to petroleum fuels, but their water, health and air pollution impacts are still uncertain. This is explained by the fact that most published TEAs and LCAs of algal systems are not supported by high-resolution models and can only provide average sustainability metrics based on results from restricted data sources. These assessments often lack the resolution to correctly analyze the temporal and regional variations of biomass yields which have a direct impact on TEA and LCA metrics. Based on the current state of the field, there is a critical need to develop dynamic models that can inform sustainability assessments and consequently assist decision-making and technology development. This first part of this research work focuses on establishing the foundations for spatially explicit and temporally resolved LCA and TEA by developing and validating models that capture the thermal and biological dynamics of open algal cultivation systems. The modeling work is heavily focused on providing accurate predictions of evaporation losses in open algae raceway ponds and investigating the effects of evaporation rates on pond temperatures and growth rates. To date, this is the first modeling effort focused on predicting the evaporation losses of open algal ponds at the commercial scale. The outputs from the thermal model are then used to inform a biological algae growth model that is validated with experimental data representing the current biomass productivity potential. When integrated with hourly historical weather data, the modeling tools provide spatiotemporal mass and energy balances of the algal cultivation, dewatering, and conversion to fuel processes. These results are then leveraged with sustainability tools such as LCA and TEA to provide sustainability metrics at a high temporal and spatial scale. After developing a robust modeling framework, the modeling tool is leveraged with two distinct water LCA methods to provide a comprehensive assessment of the water impacts of algae-derived renewable diesel production across the United States. First, a water footprint analysis is conducted to understand the direct freshwater and rainwater consumption of algal cultivation and provide a framework for comparison to traditional biofuel feedstocks. The second method provides a county-level water scarcity footprint by analyzing the impact of algal systems on local water demand and availability. This assessment allows for the proper identification of potential algal sites for algal cultivation and locations where the deployment of algal systems will exacerbate local water stress. Ultimately, this research chapter provides the first holistic investigation of the water consumption and environmental water impacts of algal systems across the U.S. and establishes benchmarks for comparison to other fuels. Finally, the work comprising the third research chapter includes a novel global sustainability assessment that integrates the developed process modeling framework with regional-specific TEA and LCA. The spatially explicit TEA considers regional labor costs, construction factors, and tax rates to assess the economic viability of algal biofuels across 6,685 global locations. Similarly, a well-to-wheels LCA was performed by accounting for the regional life cycle impacts associated with electricity generation, hydrogen, and nutrient production across ten different environmental categories including health, air pollution, and climate impacts. This framework enables the identification of algal sites with optimal productivity potential, environmental impacts, and economic viability. Discussion focuses on the challenges and opportunities to reduce costs and environmental impacts of algal biofuels in various global regions.
Keywords: climate change; techno-economic; water footprint; life cycle assessment; biomass; transportation